Behaviour of precast concrete beam-to-column connection with hidden corbel - 339664 Ling, Tieng Kooi (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2005